2018
DOI: 10.3390/biom8030053
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Epidermal Growth Factor Receptor (EGFR) Gene Polymorphisms and Lung Cancer Risk

Abstract: Lung cancer is the leading cause of cancer death globally. The epidermal growth factor receptor (EGFR) plays an important role in cell proliferation and signaling. In this study, we examined the association between EGFR gene polymorphisms and lung cancer risk among the Jordanian population. A total of 129 patients with primary lung cancer and 129 matched healthy controls were recruited into this study. EGFR rs712829, rs712830, rs2072454, and rs11543848 single nucleotide polymorphisms (SNPs) were genotyped to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Autophosphorylation of EGFR tyrosine kinase domains leads to activation of downstream proteins that mediate cell proliferation and cell survival 6 and was reported to play an important role in tumorigenesis and progression of lung adenocarcinomas 7. The EGFR gene was reported to harbor mutations and/or polymorphisms that increase susceptibility to lung cancer 8. Most of these mutations/polymorphisms exist within the catalytic kinase domain, which increases EGFR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Autophosphorylation of EGFR tyrosine kinase domains leads to activation of downstream proteins that mediate cell proliferation and cell survival 6 and was reported to play an important role in tumorigenesis and progression of lung adenocarcinomas 7. The EGFR gene was reported to harbor mutations and/or polymorphisms that increase susceptibility to lung cancer 8. Most of these mutations/polymorphisms exist within the catalytic kinase domain, which increases EGFR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, certain EGFR genetic variations have also been shown to change EGFR protein levels in the body, including lungs (Nie et al, 2015), and subsequently modulate cancer susceptibility. In accordance with this, the variations in EGFR gene have been shown to modulate risk of several types of cancers, including gastric (Torres-Jasso et al, 2015), bladder (Chu et al, 2013), breast (Sobti et al, 2012) and lung cancer (Bashir et al, 2018;Feng et al, 2014;X. Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…In Jordan, lung cancer is the third most common cancer, following breast and colorectal cancers (Ismail et al, 2013). A recent study has shown an association between EGFR rs712829 and rs2072454 SNPs with the risk of lung cancer among Jordanians (Bashir et al, 2018). In the current investigation, the relationship between two other SNPs in EGFR (rs2233947 and rs884225) and lung cancer risk was studied.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…EGFR activation by metals has been supposed to be involved in some neurodegenerative diseases [29,30]. To date, genetic studies have demonstrated that EGFR polymorphisms may modify the risk for head and neck squamous cell carcinoma (HNSCC), lung cancer, renal cancer, and so on [31][32][33]. Nevertheless, there were no studies about the relationship between metals, kidney function, and EGFR polymorphisms.…”
Section: Discussionmentioning
confidence: 99%